Предмет: Алгебра, автор: ktr18

помогите решить пожалуйста буду очень благодарен ​

Приложения:

ktr18: помогите

Ответы

Автор ответа: SofiaAva
0

Ответ:

Объяснение:

1. a) (n - 2) 2= n (2) - 2n * 2 +2(2)

n(2) - 4n +4

b)(2a+3b)(2) = (2a)(2) + 2* 2a *3b + (3b) (2) = 4a(2) + 12ab + 9b (2)

v)( x -5)(x+5)=x(2) -5(2)=x(2)-25

g)(4x-y)(y+4x)=(4x-y)(4x+y)=16x(2) - y(2)

2. a) (a+2b)(2) - (3a - b)= (a+3b - ( 3a-b))(a+3b+(3a-b))=(a+3b- 3a+b )( a+3b+3a-b)= (-2a+4b)(4a +2b)= (-2(a-2b)(2a+b)= -2*2(a-2b)(2a+b)= -4(a-2b)(2a+b).

b) a-b(2) -b+a(2)= a+(a-b)*(a+b)-b=(a-b)(1+a+b).

Похожие вопросы
Предмет: Математика, автор: nizenkos247